Method for rapidly preparing superfine copper powder from waste lithium ion battery leachate
By reacting with ascorbic acid and copper powder in the waste lithium-ion battery leaching liquid, high-purity ultrafine copper powder was successfully prepared, solving the problems of copper ion removal difficulties and other metal losses in the prior art, and achieving an efficient and simple copper recycling process.
Patent Information
- Application Number
- CN202411692618.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively remove copper ions in waste lithium-ion battery leaching liquid, and the traditional method is complex to operate, which easily causes losses of other metal ions and has a low recovery value.
Ascorbic acid is used as reducing agent and copper powder as nucleation agent. Through stirring and reaction, the copper ions in the leaching solution are precipitated into ultrafine copper powder, with an average particle size of D50 not exceeding 5 μm.
The copper ions in the leaching solution are efficiently recovered, and the ultrafine copper powder prepared has high purity, with a maximum recovery rate of 99%, and the loss rate of other metal elements does not exceed 5%, making it simple to operate.
Smart Images

Figure CN119530548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of environmental protection, and in particular to a method for quickly preparing ultrafine copper powder from waste lithium-ion battery leaching solution. Background Art
[0002] Waste lithium batteries contain a large amount of metal elements. Recycling these metal elements can reduce resource waste, solve resource shortages, protect the environment, and increase economic benefits.
[0003] With the rapid growth in demand and production of lithium-ion batteries in recent years, the amount of waste lithium-ion batteries has also increased day by day. Waste lithium-ion batteries contain a large amount of valuable metals and are a secondary resource with extremely high recycling value. The main method for recycling waste ion batteries is to use wet acid leaching to extract the valuable metals therein. The leachate usually contains a large amount of metal ions such as lithium, cobalt, nickel, manganese, and copper, and copper ions are usually treated as impurity ions in the leachate of waste ion batteries. In order to ensure the purity of the recovered products of valuable metals such as lithium, cobalt, nickel, and manganese, copper ions need to be fully removed before recycling these valuable metals. Since copper belongs to the same main group element as cobalt, nickel, and manganese, their properties are relatively similar and it is difficult to fully remove and separate them. At present, the main methods for removing copper ions in the leachate of waste ion batteries are precipitation and extraction. Precipitation is removed in the form of copper hydroxide by adjusting the pH of the leachate. The product purity is not high and the recovery value is low. The extraction method uses an organic extractant to extract and separate copper ions from the leachate, and then recovers copper in the form of copper sulfate through sulfuric acid stripping. However, this method is complicated to operate and will cause the loss of metal ions such as nickel, cobalt, and manganese. The value of the copper sulfate product is also low. Summary of the invention
[0004] In view of this, the present invention provides a method for quickly preparing ultrafine copper powder from waste lithium-ion battery leachate, which can recover copper ions in the leachate and has a small particle size of the prepared copper powder.
[0005] The technical solution is as follows:
[0006] A method for rapidly preparing ultrafine copper powder from waste lithium-ion battery leachate, wherein the method comprises: preparing battery leachate using waste lithium-ion batteries, adding ascorbic acid as a reducing agent and copper powder as a nucleating agent to the battery leachate, stirring and reacting, so that the copper ions in the battery leachate are recovered in the form of ultrafine copper powder, wherein the average particle size D of the ultrafine copper powder is 50 Not more than 5μm.
[0007] The invention adopts ascorbic acid as a reducing agent and copper powder as a nucleating agent. The nucleating agent is the same as the metal element to be recovered. The recovered metal powder basically does not contain other impurities and has high purity. The method provided by the invention is simple and easy to operate.
[0008] The ultrafine copper powder in the present invention refers to the average particle size D 50 Copper powder no larger than 5 microns.
[0009] In some embodiments, preferably, the amount of the copper powder of the nucleating agent added per liter of the battery leachate is 20-50 g / L. The amount of the nucleating agent not only affects the recovery rate of copper ions, but is also directly related to the loss rate of other metal elements in the leachate. When the amount of the nucleating agent is 20-50 g / L (such as 20 g / L, 30 g / L, 40 g / L, 50 g / L, etc.), the recovered Cu 2+ The loss of other metal ions in the battery leachate after recovery does not exceed 5%, so other metal elements can be further recovered to maximize the economic benefits.
[0010] In some embodiments, preferably, the reducing agent ascorbic acid and the Cu in the battery leachate 2+ The molar ratio of Cu is 3-10:1. 2+ Complete reduction, ascorbic acid and Cu 2+ The molar ratio can be any value within the range consisting of any two numbers among 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and 10:1.
[0011] In some embodiments, preferably, the reaction temperature is 70-90°C and the reaction time is 80-180 min. The reaction time and temperature are directly related to Cu 2+ The recovery rate can reach up to 98.5% by adopting the time and temperature of the present invention. The reaction temperature can be any value within the range of any two numbers consisting of 70°C, 75°C, 80°C, 85°C, and 90°C. The time can be any value within the range of any two numbers consisting of 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min, and 180min.
[0012] In some embodiments, preferably, the stirring speed is 100-200 rpm. The stirring speed is related to whether the reaction is thorough. The stirring speed of the present invention is conducive to improving the recovery rate. The stirring speed can be any value within the range of any two numbers of 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm, and 200 rpm.
[0013] In some embodiments, preferably, the average particle size D of the nucleating agent copper powder is 50The particle size of the copper powder of the nucleating agent can be 100 microns, 150 microns, 200 microns, 250 microns, 300 microns, preferably 150 microns. The copper powder within this particle size range can be selected to separate the nucleating agent from the obtained ultrafine copper powder by screening separation in the later stage.
[0014] In some embodiments, preferably, the Cu in the battery leachate is 2+ The concentration of Cu is 0.1-100 g / L. 2+ Applicable to waste liquid, for Cu 2+ Wastewater with low content still has good recovery effect. Cu 2+ The concentration can be any value within the range consisting of any two numbers among 0.1g / L, 0.5g / L, 1g / L, 5g / L, 10g / L, 20g / L, 50g / L, 60g / L, 80g / L, 90g / L, and 100g / L.
[0015] In some embodiments, preferably, the other metal ions in the battery leachate include lithium ions, nickel ions, cobalt ions, manganese ions and aluminum ions, wherein the concentration of the lithium ions is 0-40 g / L, the concentration of the nickel ions is 0-100 g / L, the concentration of the cobalt ions is 0-100 g / L, the concentration of the manganese ions is 0-100 g / L, and the concentration of the aluminum ions is 0.1-50 g / L. The present invention is applicable to leachates with more complex metal element contents, and the loss rate of other metal ions after the method of the present invention is not more than 5%.
[0016] In some embodiments, preferably, the preparation method of the battery leachate comprises: removing the outer shell of the waste lithium-ion battery, and then crushing and grinding the remaining part into battery powder with a particle size not exceeding 150 μm, adding H2O2 as a reducing agent and 0.2-0.5 mol / L citric acid as a leaching agent, and immersing at 60-100°C for 60-100 minutes. The waste lithium-ion battery of the present invention can be LiNi x Co y Mn z Any lithium-ion battery such as O2 (0<x<1, 0≤y<1, 0≤z<1), LiCoO2, LiFePO4, etc.
[0017] In some embodiments, preferably, the volume ratio of the mass of the battery powder to the citric acid solution is 50-120 g / L, and the volume ratio of the H2O2 to the citric acid solution is 5-25%.
[0018] Compared with the prior art, the invention has the following advantages: using metal Cu powder as nucleating agent can greatly improve the Cu 2+The precipitation rate is reduced, the reaction time is shortened, and ultrafine copper powder is quickly prepared. The preparation method is simple, and the prepared ultrafine copper powder has high added value. 2+ The recovery rate can reach up to about 99%, and the recovered Cu 2+ After that, the loss rate of other metal elements does not exceed 5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the XRD pattern of the ultrafine copper powder prepared in Example 1;
[0020] Figure 2 This is the SEM image of the ultrafine copper powder prepared in Example 1. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0023] The present invention is further described below in conjunction with embodiments and drawings.
[0024] In the following examples and comparative examples, unless otherwise specified, the reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased from the market. If no specific conditions are indicated in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed.
[0025] The content of each metal element in the leachate was measured by inductively coupled plasma mass spectrometry (ICP) method;
[0026] The particle size of copper powder was measured by scanning electron microscopy (SEM);
[0027] The copper recovery rate was calculated by using ICP to detect and analyze the copper ion concentration in the solution before reduction precipitation and the copper ion concentration after precipitation, and the following formula (1) was used for calculation:
[0028]
[0029] Where P is the copper recovery rate, C0 is the copper ion concentration in the original leaching solution, g / L; V0 is the volume of the original leaching solution, L; C t Copper ion concentration in the leaching solution after precipitation, g / L; V t is the volume of the leachate after the precipitation is completed, L.
[0030] The purity of the copper powder was measured by the leaching and dissolution method, that is, a certain mass of copper powder was weighed and completely dissolved in a 0.5 mol / L dilute sulfuric acid solution. The concentration of copper ions in the leaching solution was then analyzed by ICP detection, and the purity was calculated according to formula (2).
[0031]
[0032] Where S is the purity of copper powder, C is the concentration of copper ions in the solution, g / L; V is the volume of the solution, L; and m is the mass of the dissolved copper powder, g.
[0033] Preparation Example 1
[0034] Used lithium-ion batteries (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) was used as the test sample to prepare the battery leaching solution, and the specific operation was as follows:
[0035] The outer shell of the waste lithium-ion battery was removed, and the remaining part was crushed and ground into battery powder with a particle size of about 150 μm. 1 L of 0.5 mol / L citric acid solution was added as a leaching agent for every 100 g of battery powder, and 0.2 L of H2O2 was added as a reducing agent. The battery was immersed at 80°C for 80 min to obtain a battery leachate. The specific content of each metal element in the battery leachate is shown in Table 1.
[0036] Table 1 Metal element content
[0037]
[0038] The following Examples 1-7 all use the battery leachate prepared as described above as the test sample.
[0039] Example 1
[0040] Take the battery leaching solution prepared in Preparation Example 1, add ascorbic acid and copper powder with a particle size of 150 microns, wherein the ascorbic acid and the Cu in the battery leaching solution are 2+The molar ratio is 3:1, and 40g of copper powder is added per liter of the battery leachate;
[0041] The mixture was stirred at 150 rpm and reacted at 80 °C for 80 min. The obtained product was washed with deionized water for 3 times to obtain an average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.9%.
[0042] The XRD pattern of the obtained ultrafine copper powder is as follows: Figure 1 As shown, it can be seen that the obtained powder is all copper powder, and no other metal impurities can be observed; its SEM image is as follows Figure 2 As shown in the figure, it can be seen that the average particle size D of the copper powder is obtained. 50 It is about 5μm and is an ultrafine copper powder.
[0043] In this embodiment, the recovery rate of copper powder is 98.45%, and the loss of other metal elements does not exceed 3%.
[0044] Example 2
[0045] Take the battery leaching solution prepared in Preparation Example 1, add ascorbic acid and copper powder with a particle size of 100 microns, wherein the ascorbic acid and the Cu in the battery leaching solution are 2+ The molar ratio is 7:1, and 20g of copper powder is added per liter of the battery leachate;
[0046] The mixture was stirred at 200 rpm and reacted at 90°C for 100 min. The obtained product was rinsed with deionized water for 3 times to obtain an average particle size D 50 The ultrafine copper powder has a diameter of 4 μm and a purity of 99.9%.
[0047] In this embodiment, the recovery rate of copper powder is 97.0%, and the loss of other metal elements does not exceed 3%.
[0048] Example 3
[0049] Take the battery leaching solution prepared in Preparation Example 1, add ascorbic acid and copper powder with a particle size of 300 microns, wherein the ascorbic acid and the Cu in the battery leaching solution are 2+ The molar ratio is 5:1, and 50g of copper powder is added per liter of the battery leachate;
[0050] The mixture was stirred at 100 rpm and reacted at 70°C for 180 min. The obtained product was rinsed with deionized water three times to obtain an average particle size D 50 The ultrafine copper powder is 3 μm in diameter and has a purity of 99.8%.
[0051] In this embodiment, the recovery rate of copper powder is 98.98%, and the loss of other metal elements does not exceed 5%.
[0052] Example 4
[0053] The process was carried out in the same manner as in Example 1, except that 60 g of copper powder was added per liter of the battery leaching solution.
[0054] The average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.5%.
[0055] In this embodiment, the recovery rate of copper powder is 99.04%, and the loss of other metal elements reaches 6%.
[0056] Example 5
[0057] The process was carried out in the same manner as in Example 1, except that 80 g of copper powder was added per liter of the battery leaching solution.
[0058] The average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.5%.
[0059] In this embodiment, the recovery rate of copper powder is 99.26%, and the loss of other metal elements reaches 8%.
[0060] Example 6
[0061] The process was carried out in the same manner as in Example 1, except that the reaction temperature was 50°C.
[0062] The average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.9%.
[0063] In this embodiment, the recovery rate of copper powder is 64.63%, and the loss of other metal elements does not exceed 3%.
[0064] Example 7
[0065] The process was carried out in the same manner as in Example 1, except that the reaction time was 50 min.
[0066] The average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.9%.
[0067] In this embodiment, the recovery rate of copper powder is 94.23%, and the loss of other metal elements does not exceed 3%.
[0068] Example 8
[0069] The method of Example 1 is followed, except that ascorbic acid and Cu in the battery leachate 2+ The molar ratio is 1:1.
[0070] The average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.9%.
[0071] In this embodiment, the recovery rate of copper powder is 70.27%, and the loss of other metal elements does not exceed 3%.
[0072] Example 9
[0073] The method of Example 1 is followed, except that ascorbic acid and Cu in the battery leachate 2+ The molar ratio is 10:1.
[0074] The average particle size D 50 The ultrafine copper powder has a diameter of 5 μm and a purity of 99.9%.
[0075] In this embodiment, the recovery rate of copper powder is 98.95%, and the loss of other metal elements does not exceed 3%.
[0076] Comparative Example 1
[0077] The method of Example 1 is followed, except that only ascorbic acid is added, and no nucleating agent copper powder is added. The particle size of the copper powder obtained is 4 μm and the purity is 99.9%.
[0078] In this example, the recovery rate of copper powder is 50.24%, and the loss of other metal elements exceeds 2%.
[0079] Comparative Example 2
[0080] The method of Example 1 is followed, except that the copper powder is replaced by iron powder of the same particle size.
[0081] The copper powder thus obtained had a particle size of 5 microns and a purity of 90.57%;
[0082] In this example, the recovery rate of copper powder is 94.34%, and the loss of other metal elements is about 3%.
[0083] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, ordinary technicians in this field can make various similar expressions without violating the purpose and claims of the present invention, and such changes all fall within the scope of protection of the present invention.
Claims
1. A method for rapidly preparing ultrafine copper powder from waste lithium-ion battery leachate, characterized in that: The method comprises: preparing a battery leachate using waste lithium-ion batteries, adding a reducing agent ascorbic acid and a nucleating agent copper powder to the battery leachate, stirring and reacting, so that the copper ions in the battery leachate are recovered in the form of ultrafine copper powder, wherein the average particle size D of the ultrafine copper powder is 50 Not more than 5μm.
2. The method according to claim 1, characterized in that The amount of the nucleating agent copper powder added per liter of the battery leaching solution is 20-50 g / L.
3. The method according to claim 1 or 2, characterized in that: The reducing agent ascorbic acid and the Cu in the battery leaching solution 2+ The molar ratio is 3-10:
1.
4. The method according to any one of claims 1 to 3, characterized in that: The reaction temperature is 70-90°C and the reaction time is 80-180 minutes.
5. The method according to any one of claims 1 to 4, characterized in that: The stirring speed is 100-200 rpm.
6. The method according to any one of claims 1 to 5, characterized in that: The average particle size D of the copper powder of the nucleating agent 50 100-300 microns.
7. The method according to any one of claims 1 to 6, characterized in that: The battery leaching solution contains Cu 2+ The concentration is 0.1-100g / L.
8. The method according to any one of claims 1 to 7, characterized in that: Other metal ions in the battery leachate include lithium ions, nickel ions, cobalt ions, manganese ions and aluminum ions, wherein the concentration of the lithium ions is 0-40 g / L, the concentration of the nickel ions is 0-100 g / L, the concentration of the cobalt ions is 0-100 g / L, the concentration of the manganese ions is 0-100 g / L, and the concentration of the aluminum ions is 0.1-50 g / L.
9. The method according to any one of claims 1 to 8, characterized in that: The preparation method of the battery leachate comprises: removing the shell of the waste lithium-ion battery, then crushing and grinding the remaining part into battery powder with a particle size not exceeding 150 μm, adding H2O2 as a reducing agent and 0.2-0.5 mol / L citric acid solution as a leaching agent, and immersing at 60-100° C. for 60-100 minutes.
10. The method according to claim 9, characterized in that The mass ratio of the battery powder to the volume ratio of the citric acid solution is 50-120 g / L, and the volume ratio of the H2O2 to the citric acid solution is 5-25%.